2014
DOI: 10.1039/c3nr06599e
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable nanoassemblies of piperlongumine display enhanced anti-angiogenesis and anti-tumor activities

Abstract: Piperlongumine (PL) shows an inhibitory effect on tumor growth; however, lipophilicity has restricted its further applications. Nanotechnology provides an effective method to overcome the poor water solubility of lipophilic drugs. Polymeric micelles with small particle size can passively target tumors by the enhanced permeability and retention (EPR) effect, thus improving their anti-tumor effects. In this study, to improve the water solubility and anti-tumor activity of PL, PL encapsulated polymeric micelles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…Piperlongumine induced ROS accumulation in primary human myeloid leukemia cells PL is considered a cancer cell-specific ROS inducer [10] , and previous studies have demonstrated that PL induced ROS accumulation in various cancer cell lines [19][20][21] . We determined the level of intracellular ROS in PL-treated BMMNCs using the fluorescent ROS indicator DCFH-DA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Piperlongumine induced ROS accumulation in primary human myeloid leukemia cells PL is considered a cancer cell-specific ROS inducer [10] , and previous studies have demonstrated that PL induced ROS accumulation in various cancer cell lines [19][20][21] . We determined the level of intracellular ROS in PL-treated BMMNCs using the fluorescent ROS indicator DCFH-DA.…”
Section: Resultsmentioning
confidence: 99%
“…The final concentration of DMSO was less than 0.1%. N-acetyl-L-cysteine (NAC, antioxidant, Sigma- [20] 45, X, -X, t(8;21)(q22;q22) [20] 46, XX, t(9;22)(q34;q11) [60] 47, XX, t(10;11)(p12;q23)+mar [7] /46, XX [3] 46, XX, t(9;11)(p12;q23) [20] 46, XX, N [20] No split phase 46, XY, t(9;22)(q34;q11) [38] 46, XX [20] 46, XX, del(2)(p11), del(3)(p12), del(3)(p26), del(3)(q13), del(4)(q31), del(6)(p23), del(7)(q22q34), -10, del(12) (p12), del(13)(q12q14), +15, -16, -21, +mar[cp10] 46, XY [12] www.nature.com/aps Xiong XX et al Acta Pharmacologica Sinica npg Aldrich, St Louis, MI, USA) was used at 3 mmol/L, whereas SB203580 (P38 pathway-specific inhibitor, Cell Signaling Technology, Danvers, MA, USA) and SP600125 (JNK pathwayspecific inhibitor, Cell Signaling Technology) were used at 10 µmol/L. NAC, SB203580, and SP600125 were added 1 h before PL-treatment.…”
Section: Methodsmentioning
confidence: 99%
“…According to Fig. 9B-D, tumor volume, length of tumor-induced blood vessels and branch points of tumor-induced blood vessels were dramatically inhibited in Che-M group (3.70 AE 1.14 Â 10 À3 mm 3 and 167.7 AE 68.2 mm, 9.2 AE 4.0, respectively) compared with those in free chetomin (7.15 AE 1.59 Â 10 À3 mm 3 , P < 0.001; 337.0 AE 72.6 mm, P < 0.001; 18.5 AE 3.9, P < 0.001, respectively), blank micelles (12.78 AE 2.14 Â 10 À3 mm 3 , P < 0.001; 895.0 AE 136.8 mm, P < 0.001; 45.8 AE 5.8, P < 0.001, respectively), or normal saline (11.77 AE 2.11 Â 10 À3 mm 3 , P < 0.001; 840.7 AE 126.8 mm, P < 0.001; 42.0 AE 7.3, P < 0.001, respectively) group. The above results suggested that Che-M could dramatically inhibit both embryonic and tumor-induced angiogenesis.…”
Section: Antitumor and Antiangiogenesis Evaluation In Tumor Xenogra mentioning
confidence: 93%
“…Mice were injected subcutaneously with 100 mL of CT26 cell suspension containing 5 Â 10 5 cells in the right ank. When the volume of tumors was approximately 200 mm 3 , tumor bearing mice were randomized into three groups, which were injected intravenously with 100 mL…”
Section: Determination Of Chetomin Concentration In Tumorsmentioning
confidence: 99%
See 1 more Smart Citation